Evaluation of fluralaner as a novel treatment for Scabies in naturally infested dogs - Sharma, Pardeep; Bansal, Abhishek (Indian Journal of Veterinary Medicine, 2024)
A single treatment of fluralaner orally once is sufficient and safe to kill Sarcoptes mites and improve the clinical condition of diseased dogs. Sarcoptes mite was detected in eight dogs having the presence of pinnalpedal reflex and having sarcoptic mange-related skin lesions (erythema, alopecia, papule, crust etc.). Skin scrappings were taken from at least five different body areas judged to be most likely to have mean mite infestation on the days 0, 28, 56, and 84 and improvement in resolution of skin lesions was assessed on days 28, 56, and 84. On day 28th after treatment, all dogs were completely parasitological cured and most of the dermatological lesions were resolved on day 28th and completely resolved on days 56th and 84th. Marked alterations in the haemato-biochemical panels were observed as compared to healthy dogs. All studies of haemato-biochemical panels improved towards normalcy on day 56 post-treatment showing encouraging response to the therapy.